Aerospace Journals – Metrics & Ranking (DGLR - Top 40 - Aerospace Journal Ranking) - Dieter Scholz (Deutsche Gesellschaft für Luft- und Raumfahrt, 2015)
The current discussions about publication ethics, impact factor, Google, and Open Access cause much confusion. With respect to aerospace journals, a listing of parameters and a ranking may be the first step to understand available options for authors and could guide them to where to publish. Journals with a general focus on aeronautical engineering or space engineering were selected to take part in the ranking. Journals were selected from existing aerospace journal rankings e.g. Google Scholar and Scopus (CWTS and SJR). These three metrics were selected: Impact Factor, Google Scholar h5-Index, SNIP (Source Normalized Impact per Paper) from Scopus. The average of these three journal rankings was the base for the final score and the so called "DGLR – Top 40 – Aerospace Journal Ranking". The ranking is named after the German Society for Aeronautics and Astronautics (DGLR) because this is the place selected to publish the results prominently (http://l2.dglr.de). The Journal "Progress in Aerospace Science" was ranked number one in this year's ranking. It was observed that US American journals dominate the market and also this journal ranking. There are only few Open Access journals available. This is especially true for the top 40 in this journal ranking. The "DGLR – Top 40 – Aerospace Journal Ranking" could be updated with newly available data in June each year!
Keywords: aerospace; journal; metrics; selection; journal; open access; ranking; Google; Scopus; Impact Factor